TINGGALAN KOLONIAL DI PULAU DOOM - Sukandar, Sri Chiirullia (BALAI ARKEOLOGI PAPUA, 2012)
Doom Island administratively included in the Islands Sorong District, City of Sorong, West Papua Province. Island of Doom was formerly the seat of government Onderafdeling (subsections) Raja Ampat placed an HPB (Hoofd van Plaatselijk bestuur). Until the 1950’s Island of Doom a warehousing hub and trading port of Sorong. It is estimated there are many buildings of the colonial legacy infrastructure to support the purposes of Dutch life Doom Island.